Xử lý kết quả phân tích độ hạt bằng phương pháp Toán Tin - Minh, Đàm Quang; Nhàn, Trần Thanh; Tâm, Nguyễn Văn; Thành, Đinh Xuân (Vietnam Journal of Earth Sciences, 2002)
Treating the results of analyzing grain size with the mathematic-informative method